Politically connected audit committees and ESG reporting - Kusharyanti; Astuti, Sri; Marita (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2024)
This study investigates the impact of audit committees with political connections on environmental, social, and governance (ESG) reporting. Drawing from reputational cost theory, it hypothesizes that personal political affiliations of audit committee members positively influence ESG reporting quality. Analyzing data from companies listed on the Indonesia Stock Exchange between 2018 and 2022, the findings reveal that companies with politically connected audit committees exhibit higher levels of ESG reporting compared to their counterparts without such connections. The study highlights that audit committees with political ties are subject to increased litigation risks and reputational costs.